Abandoned to Ourselves. - Meyers, Peter Alexander (Yale University Press, 2013)
In 'Abandoned to Ourselves', Peter Alexander Myers shows how the centrepiece of the Enlightenment - society as the symbol of collective human life and as the fundamental domain of human practice - was primarily composed and animated by its most ambivalent figure: Jean-Jacques Rousseau.